Design and evaluation of a sequence capture system for genome-wide SNP genotyping in highly heterozygous plant genomes: a case study with a keystone Neotropical hardwood tree genome. (17th July 2018) - Silva-Junior, Orzenil Bonfim; Grattapaglia, Dario; Novaes, Evandro; Collevatti, Rosane G
Abstract: Targeted sequence capture coupled to high-throughput sequencing has become a powerful method for the study of genome-wide sequence variation. Following our recent development of a genome assembly for the Pink Ipê tree ( Handroanthus impetiginosus ), a widely distributed Neotropical timber species, we now report the development of a set of 24, 751 capture probes for single-nucleotide polymorphisms (SNPs) characterization and genotyping across 18, 216 distinct loci, sampling more than 10 Mbp of the species genome. This system identifies nearly 200, 000 SNPs located inside or in close proximity to almost 14, 000 annotated protein-coding genes, generating quality genotypic data in populations spanning wide geographic distances across the species native range. To provide recommendations for future developments of similar systems for highly heterozygous plant genomes we investigated issues such as probe design, sequencing coverage and bioinformatics, including the evaluation of the capture efficiency and a reassessment of the technical reproducibility of the assay for SNPs recall and genotyping precision. Our results highlight the value of a detailed probe screening on a preliminary genome assembly to produce reliable data for downstream genetic studies. This work should inspire and assist the development of similar genomic resources for other orphan crops and forest trees with highly heterozygous genomes.